Satu Langkah Melawan Bullying, Sejuta Senyum Tercipta: Edukasi Pencegahan Perundungan Pada Peserta Didik Sekolah Dasar Di Desa Muaradua - Hikmatullah Hikmatullah; Puput Handayani; Muhammad Ridho Rizqulloh; Aal Mujadilah Aal Mujadilah; Abi Muarif Fajrin; Dea Puspita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Bullying is a form of violence that may occur in educational environments and can have negative impacts on students’ physical, psychological, social, and academic development. Limited understanding of the various forms of bullying may lead students to perceive bullying behavior as merely a joke in their daily interactions. This community service activity aimed to increase students’ knowledge and awareness of bullying and to promote the creation of a safe, comfortable, and bullying-free school environment. The activity was conducted on August 10, 2026, at SD Negeri 3 Muaradua, Cikulur District, Lebak Regency, Banten Province, involving 54 students. The method employed an educational-participatory approach through material presentation, interactive discussions, reflection, simple case studies, and evaluation of students’ understanding through question-and-answer sessions. The materials covered the definition of bullying, various forms of bullying, contributing factors, its impacts on victims, prevention strategies, and appropriate actions to take when experiencing or witnessing bullying. The results of the activity indicated an improvement in students’ understanding of bullying. Furthermore, the participants demonstrated enthusiasm and active involvement throughout the educational session. This activity demonstrates that interactive anti-bullying education can serve as a preventive effort to increase students’ awareness and foster a positive school culture.